Comparison of different settings for yellow subthreshold laser treatment in diabetic macular edema - Chhablani, Jay (BMC Ophthalmol, 2018)
BACKGROUND: To assess the safety and efficacy of two subthreshold parameters (5 and 15% duty cycle (DC)) compared to standard ETDRS (early treatment of diabetic retinopathy study) continuous wave (CW) laser. METHODS: In this prospective randomized study, 30 eyes from 20 patients with non-center involving macular edema were randomized into 3 different groups: 5% DC, 15% DC and CW navigated modified ETDRS laser treatment. Titration in subthreshold groups was performed with 30% of the threshold power, decided with microsecond pulses. CW laser was titrated to a barely visible burn. All patients underwent microperimetry, thickness measurements and visual acuity examinations at baseline, 6 weeks and 12 weeks post treatment. RESULTS: At three months follow up, retinal sensitivity was significantly reduced in the CW group by − 2.2 dB whereas in both subthreshold groups, retinal sensitivity increased by 2.4 dB for 5% and 1.9 dB for 15% DC with no significant difference. Retinal volume (mm(3)) decreased in both subthreshold groups by 0.08 ± 0.3 and 0.12 ± 0.11 in 5 and 15% DC group respectively. Whereas the CW group showed volume increase of 0.55 ± 0.92 (p = 0.02 and 0.01 for 5 and 15% DC groups). Visual acuity remained stable in all 3 groups (− 0.7 letter in 5% DC; 2.11 letters in 15% DC and 0.88 in CW with no significant difference). CONCLUSION: Subthreshold microsecond laser was shown to be safe and effective with both 5 and 15% DC as compared to conventional photocoagulation with ETDRS parameters. The 15% DC setting trended to achieve better anatomical, visual and functional outcomes. TRIAL REGISTRATION: Retrospectively registered (NCT03571659, 06/26/2018).